Efficiency of the Halliwick concept in the rehabilitation of children with cerebral palsy - Gajić, Dragana; Jokić, Slađana; Mraković, Bogdana (Scripta Medica, 2020)
Background/Aim: Since 2010, the Halliwick Concept has been applied in the rehabilitation of children with neurological disorders at the Department of Habilitation and Rehabilitation of Children and Youth at the Institute for Physical Medicine and Rehabilitation (IPMR) "Dr Miroslav Zotović" in Banja Luka, the Republic of Srpska, Bosna and Herzegovina. Aim of this study was to analyse results of the implementation of the full Halliwick Concept programme over the period from 1 January 2016 to 1 January 2017 and points to the effectiveness of this type of hydrokinesitherapy. Methods: After analysing 40 patients with different diagnoses of neurological disorders: cerebral palsy (CP), arthrogryposis (AG), Down syndrome (DS), and central nervous system (CNS) injury, only patients with CP were represented due to the homogeneity of the diagnosis and were included in analysis (N = 30). Rehabilitation treatment of patients according to the Halliwick concept was performed, over a period of one year, for 60 minutes once a week. Patients were tested by Swimming With Independent Measurement (SWIM) test, Gross Motor Function Measure (GMFM) and Barthel Index before and after treatment.Results: Considering all patients, before and after the application of the concept of individual Halliwick swimming skills/movement in water, a statistically significant difference was detected by assessing the SWIM test and a highly significant difference was detected by evaluating the Gross motor function measure test of GMFM66, as well as in evaluating the Barthel Index test. Assessment of swimming abilities through the SWIM test showed the least progression was in the ability in Getting out of the water, with the greatest progression in the ability in Breathing control. Conslusion: The Halliwick Concept programme at the Department for the Habilitation and Rehabilitation of Children and Youth, IPMR "Dr Miroslav Zotović" in Banja Luka is effective and the results indicate the need for its application in the rehabilitation of children with CP.
Keywords: Hydrokinesitherapy; Halliwick concept; Swimming; SWIM test; C bral palsy.; Hydrokinesitherapy; Halliwick concept; Swimming; SWIM test; Cerebral palsy